Institutional Racism in American Post-Civil Rights Movement in Dear Martin by Nic Stone (2017) - Afifah Indriani; Delvi Wahyuni (Universitas Negeri Padang, 2021)
This thesis is an analysis of a novel written by Nic Stone entitled Dear Martin (2017). It explores the issue of institutional racism in the post-civil rights era. The concept of systemic racism by Joe R.Feagin is employed to analyze this novel. This analysis focuses on four issues of systemic racism as seen through several African-American characters. This analysis also depends on the narrator to determine which parts of the novel are used as the data. The result of the study shows that African-American characters experience four forms of institutional racism which are The White Racial Frame and Its Embedded Racist Ideology, Alienated Social Relations, Racial Hierarchy with Divergent Group Interest, and Related Racial Domination: Discrimination in Many Aspects. In conclusion, in this post-civil rights movement era, African-Americans still face institutional racism.